PERAN SUAMI DALAM MEMOTIVASI ISTRI MEMBERIKAN ASI EKSKLUSIF DI DESA PAJURANGAN PROBOLINGG - Fulatul Anifah (Sinar : Jurnal Kebidanan, 2019)
Objective: to know husband’s role in motivating wife to gives exclusive breastfeeding Methods: Method of this study is descriptive, using population all breastfeeding mothers. Samples collected from 30 respondents. Sampling technique that is used purposive sampling. Measuring apparatus using questionnaires then tabulated and analyzed by frequency distribution Result: Result of this study shows that most of husbands, amount 13 respondents (43,3%), play their role mediocrity in motivating wife to gives exclusive mother’s milk, 10 respondents (33,3%) have less role and 7 respondents (23,3%) have good role. Conclusion: From this study we can conclude that husband’s role in motivating wife to gives exclusive mother’s milk is mediocre. For it, we need to increase giving motivation to families by elucidation. By that, husbands understand their role and how to motivate their wife to gives exclusive breastfeedingKeywords: : husband’s role, motivation, Exclusive Breastfeeding